Pengaruh Kebijakan Hutang Dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Variabel Kontrol Ukuran Perusahaan Dan Profitabilitas (Studi pada Perusahaan Bank yang Terdaftar di BEI Tahun 2021-2023) - Entik Estifika; Hendri Setyawan (Politeknik Raflesia Press, 2025)
The purpose of this study is to determine the effect of dividend policy and debt policy on firm value, where company size and profitability are used as control variables. The research was conducted at bank companies listed on the Indonesia Stock Exchange. The research period is 2019 - 2023. The theory used is signalling theory. The type of research is quantitative. The independent variables in this study are debt policy and dividend policy. While company value as the dependent variable is measured using Tobin's Q. Company size and profitability are used as control variables. The sample was obtained using purposive sampling. A total of 84 data were used as samples because they met the criteria. The method used is multiple linear regression analysis using the SPSS version 26 application. The results showed that dividend policy has no effect on firm value. While debt policy has a positive and significant effect on firm value. The control variabl is company size, has no significant effect on firm value. Meanwhile, profitability has a negative and significant effect on firm value.